Judi Online: Faktor Pemicu Perceraian dalam Keluarga Modern - Fadillah Utami; Siti Patimah; Adenan Adenan; Darwis Mustakim (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
Online gambling has emerged as a significant cause of divorce in modern society. This study aims to analyze the impact of online gambling addiction on marital relationships. Using qualitative methods, data were collected through interviews with couples who experienced divorce due to online gambling. The findings indicate that online gambling leads to significant financial problems, loss of trust, and prolonged emotional conflicts. This research highlights the importance of raising awareness about the risks of online gambling and the need for support for affected individuals. Thus, this study provides insights into how online gambling can undermine family structure and interpersonal relationships.